2022
DOI: 10.31557/apjcp.2022.23.3.807
|View full text |Cite
|
Sign up to set email alerts
|

Determining Gastric Cancer-Related Risk Factors in Mongolian Population Using ABC(D) Method: A Matched Case-Control Study

Abstract: Objective: We aimed to identify gastric cancer-related risk factors and evaluate the efficacy of screening ABC(D) method in determining high risk gastric cancer individuals in Mongolian population. Methods: A total of 240 participants (120 gastric cancer patients and 120 healthy individuals) were included in this study. Data were collecting using a structured questionnaire consisting of 56 questions covering 5 categories. Serum Helicobacter pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…All the studies included in this systematic review indicated that a first‐degree family history of gastric cancer represents a risk factor for gastric cancer 14–43 . The studies included in our systematic review provided interesting insights through subanalyses that explored various factors, such as gender, the type of family member affected (father, mother, or sibling), the specific anatomical site of cancer (corpus/antrum), geographical risk, and age considerations.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…All the studies included in this systematic review indicated that a first‐degree family history of gastric cancer represents a risk factor for gastric cancer 14–43 . The studies included in our systematic review provided interesting insights through subanalyses that explored various factors, such as gender, the type of family member affected (father, mother, or sibling), the specific anatomical site of cancer (corpus/antrum), geographical risk, and age considerations.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, only one study described a higher risk in male individuals 38 . Additionally, the presence of siblings affected by gastric cancer was identified as a higher risk factor than a parental history of gastric cancer 17,19,20,21,24,27,29,30,36,37,41 . Furthermore, in many studies, it was documented that having a mother affected by gastric cancer represented a higher risk than having a father affected by gastric cancer 35,39,41 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation